Whither the people in the ASEAN Community?: Prospects in regional community building above and below the state. Issue 3 (1st December 2020) - Tan, See Seng
Abstract: The longstanding effort to develop a people-based regionalism in Southeast Asia has been shaped by an inherent tension between the liberal inclination to privilege the individual and the community under formation, on the one hand, and the realist insistence on the primacy of the state, on the other. This article explores the conditions and constraints affecting ASEAN's progress in remaking Southeast Asia into a people-focused and caring community in three areas: disaster management, development, and democratization (understood here as human rights). Arguably, the persistent gap in Southeast Asia between aspiration and expectation is determined less by political ideology than by the pragmatic responses of ASEAN member states to the forces of nationalism and protectionism, as well as their respective sense of local and regional responsibility. Resumen: El esfuerzo histórico para desarrollar un regionalismo basado en las personas del sudeste de Asia ha estado marcado por una tensión fundamental entre la inclinación liberal de privilegiar el individuo y la comunidad y la insistencia realista sobre la primacía del estado. Este artículo explora las condiciones y limitaciones que afectan el progreso de la ASEAN en la reestructuración de Asia sudoriental en una comunidad centrada en el cuidado de las personas en: gestión de desastres, desarrollo y democratización (i.e., derechos humanos). La brecha persistente en el sudeste asiático entre la aspiración y la expectativa está determinada por las respuestas pragmáticas de los miembros de la ASEAN sometidos a las fuerzas del nacionalismo y proteccionismo, así como su respectivo sentido de responsabilidad local y regional. Résumé: L'effort historique pour développer un régionalisme fondé sur les peuples en Asie du Sud-Est a été marqué par une tension fondamentale entre l'inclination libérale qui privilégie, d'une part, l'individu et la communauté et, d'autre part, l'insistance réaliste sur la primauté de l'État. Cet article explore les conditions et les contraintes qui nuisent aux progrès de l'ANASE dans le cadre d'une refonte de l'Asie du Sud-Est en une communauté centrée et attentive aux peuples dans trois domaines : la gestion des désastres, le développement et la démocratisation (en référence aux droits humains). Le fossé persistant en Asie du Sud-Est entre les aspirations et les attentes est vraisemblablement moins déterminé par l'idéologie politique que par les réponses pragmatiques des États membres de l'ANASE soumis aux forces du nationalisme et du protectionnisme ainsi que par leur sens respectif de la responsabilité locale et régionale.